2019
DOI: 10.1016/j.ijppaw.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution and risk factors for Echinococcus granulosus infection in peri-urban wild dog populations

Abstract: The transmission of zoonotic pathogens associated with wildlife in peri-urban environments can be influenced by the interplay of numerous socioecological factors. Echinococcus granulosus is known to be common within peri-urban wild dog populations however knowledge of the factors that influence its presence is limited. We investigated the demographic distribution of adult cestode abundance (ACA: defined as the product between prevalence of infection and adult cestode infection intensity) and the role of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
7
1
1
Order By: Relevance
“…This finding concurs with the report of Liu et al [58] from China. It however contradicts other reports from Iran [41,43], Chile [47] and Australia [51]. Our study also revealed a significantly higher prevalence of E. granulosus in stray than owned dogs.…”
Section: Echinococcus Granulosus Infection In Dogscontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding concurs with the report of Liu et al [58] from China. It however contradicts other reports from Iran [41,43], Chile [47] and Australia [51]. Our study also revealed a significantly higher prevalence of E. granulosus in stray than owned dogs.…”
Section: Echinococcus Granulosus Infection In Dogscontrasting
confidence: 99%
“…The 16.9% Africa-wide prevalence of EGI observed in dogs falls within the ranges documented elsewhere. For instance, studies from Asia reported a range of 7.3 to 48.0% [41][42][43][44], those from Latin America reported a range of 9.3 to 42.3% [45][46][47][48], and in Australia, a range of 3.16 to 50.7% was also reported [49][50][51] affirming reports that E. granulosus is cosmopolitan in distribution. The infection in these dogs may pose the risk of environmental contamination which may in turn result in the infection of intermediate hosts like domestic ruminants thereby maintaining the disease.…”
Section: Echinococcus Granulosus Infection In Dogsmentioning
confidence: 66%
“…The results of the Harriott et al . (2019) study in Queensland, Australia, showed that CE infection rate significantly increased with higher rainfall, relative humidity and temperature. Veit et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the relationship between dingoes and humans changed drastically with European settlement and the implementation of agriculture (Rogers & Kaplan, 2003). Clearing of lands and farming practices led to dingo attacks on the newly introduced livestock, and arguably the start of the friction between pastoralists and dingoes (Coman, 1972; Harriott et al., 2019; Hytten, 2009; Jones, 2009; Sloan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…and farming practices led to dingo attacks on the newly introduced livestock, and arguably the start of the friction between pastoralists and dingoes (Coman, 1972;Harriott et al, 2019;Hytten, 2009;Jones, 2009;Sloan et al, 2017).…”
mentioning
confidence: 99%